Peran Kepala Sekolah Sebagai Shepherd Leader Ketua Tim SD XYZ Kupang dalam Membangun Kerja Sama Tim Melalui Bonding Time - Irvadiarlistikaningrum, Uki Fergialita; Gunanto, Yohanes Edi (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Teamwork is one of the skills that needs to be developed in the 21st century. SD XYZ Kupang has the expectation of doing teamwork, namely through bonding time, so this is unique. Teamwork through bonding time is based on the task of pastoral leadership, namely shepherding for the community. This study aims to determine the role of school principals as pastoral leaders in implementing pastoral leadership for team leaders, teamwork implementation through bonding time for team leaders and challenges of school principals when carrying out pastoral leadership in building teamwork through bonding time for team leaders. This study uses a qualitative case study design method. The informants in this study used purposive sampling. Data collection tools are questionnaires, interviews and observations. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the research show that the implementation of shepherd leadership has been carried out namely relations, while the other six indicators have not been implemented optimally. Teamwork through bonding time has not been implemented optimally. The teamwork carried out by the school principal is communal and professional. Where these two themes are new themes that emerge from the analysis and outside of the indicators of teamwork and bonding time. The challenges are programs that have not been maximized and some task delegation activities that are not suitable to be carried out in the context of shepherding or teamwork through bonding time.